General Equilibrium Stock Index Futures Prices: Theory and Empirical Evidence - Hemler, Michael L.; Longstaff, Francis A. (Journal of Financial and Quantitative Analysis, 1991)
We develop a closed-form general equilibrium model of stock index futures prices in a continuous-time economy with stochastic interest rates and market volatility. We show that futures prices implied by the model have very different properties from those of the cost of carry model. Using NYSE stock index futures data, we examine the restrictions imposed on futures prices by both the equilibrium and cost of carry models. Consistent with the equilibrium model, we find that stock index futures prices are related to market volatility and that their interest-rate sensitivity is a nonlinear function of contract maturity.